Characterization of Clasts in the Glen Torridon Region of Gale Crater Observed by the Mars Science Laboratory Curiosity Rover. Issue 11 (17th November 2022) - Khan, Sabrina Y.; Stack, Kathryn M.; Yingst, R. Aileen; Bergmann, Kristin
Abstract: The morphology and composition of clasts have the potential to reveal the nature and extent of erosional processes acting in a region. Dense accumulations of granule‐ to pebble‐sized clasts covering the ground throughout the Glen Torridon region of Gale crater on Mars were studied using data acquired by the Mars Science Laboratory Curiosity rover between sols 2300 and 2593. In this study, measurements of shape, size, texture, and elemental abundance of unconsolidated granules and pebbles within northern Glen Torridon were compiled. Nine primary clast types were identified through stepwise hierarchical clustering, all of which are sedimentary and can be compositionally linked to local bedrock, suggesting relatively short transport distances. Several clast types display features associated with fragmentation along bedding planes and existing cracks in bedrock. These results indicate that Glen Torridon clasts are primarily the product of in‐situ physical weathering of local bedrock. Plain Language Summary: Clasts are loose fragments produced by the breakdown of rock, which can be transported and reshaped by forces like water, wind and gravity. Clast shape, size, and texture are useful indicators of the clast's origin and the forces that have transported and modified it over time. The Glen Torridon region of Gale crater, the field site for the Mars Science Laboratory Curiosity rover, is covered at the surface by an abundance of granule‐ to pebble‐sized clasts. Between Martian days ("sols") 2300 and 2593, Curiosity acquired images and compositional data of Glen Torridon clasts along the traverse. In this study, measurements of shape, size, texture, and composition of Glen Torridon granules and pebbles were compiled for characterization, and to determine their origin and erosional history. Nine primary clast types were identified, all of which are sedimentary rock and are similar in composition to the local bedrock, suggesting most clasts were transported short distances. Several clast types display features associated with fragmentation along bedding planes and existing cracks in bedrock. These results indicate that clasts in Glen Torridon are primarily the product of bedrock fragmentation. Key Points: Clasts are abundant across the surface of Glen Torridon Nine distinct clast types are identified throughout the region with different types representing distinct stages along the erosional continuum Clasts are locally sourced and represent erosional and deflationary remnants of the Jura and Knockfarril Hill members